Drop out v/s retention of female students: unfolding dynamics of the education system in Indian states - Namitarani Gochhayat; Rekha Ravindran (Discover Education)
Abstract School dropout and retention are a primary concern for society, educators, and policymakers. This study focuses on the factors affecting gender disparity in education captured in terms of enrolment, never enrolled, and dropout among Indian children. We use the National Sample Survey Office (NSSO)-75th (July 2017–June 2018) round of survey data on social consumption related to education. The study employs the Multinomial Logistic Regression (MLR) method to analyse the driving factors of educational enrolment status in male and female children. The empirical results show that female children are more likely to never enrol in school or drop out of school than male children. Further, the study also finds a notable rise in female dropout rates (0.231) among the age group of 16–18, whereas male dropout rates increase by 0.192 in the same age group.